Implementasi Kurikulum Merdeka Dalam Pembelajaran Pendidikan Agama Islam - Qolbiyah, Aini (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This paper discusses innovations in Islamic religious education which are very basic things and need to be implemented. The policy of